A novel structure of dithered nested digital delta sigma modulator with low-complexity low-spur for fractional frequency synthesizers. Issue 1 (4th January 2016) - Sadat Noori, Seyed Ali; Farshidi, Ebrahim; Sadoughi, Sirus
Abstract : Purpose: – Digital Delta Sigma Modulator (DDSM) is used widely in electronic circuits including Radars, class-D power amplifiers and fractional frequency synthesizers. The purpose of this paper is to propose an implementation for MASH DDSMs named as Multi Modulus Reduced Complexity (MMRC) architecture. Design/methodology/approach: – This architecture will use a very simple pseudorandom Linear Feedback Shift Register (LFSR) dither signal with period N_d to randomize the digital MMRC modulator used for fractional frequency synthesizers. Using error masking methodology, the MMRC modulator can decrease the hardware consumption and increase accuracy of the fractional frequency synthesizer. Rules for selecting the appropriate word lengths of the constituent MMRC modulator are derived. Findings: – This paper contains three modulators. The first stage modulator is a variable modulus First Order Error Feedback Modulator and has a programmable modulus M1 that is not a power of two. The second and third stage modulators are the first order pseudorandom LFSR dithered MASH 1-1 and modified MASH 1-1-1, which have conventional modulo M2, M3, respectively. With optimum selection modulus M1, the new structure can synthesize the desired frequency exactly. Simulation results confirm the theoretical predictions. Also the results of circuit implementation proposed method reports 13 per cent reduction in hardware. Originality/value: – This paper for the first time proposes a nested sigma delta modulator with a pseudorandom shaped dither signal which reduced hardware complexity and increased the period of output signal. This modulator is exploited in the fractional frequency synthesizer to the output frequency can be set more accurately.